2021
DOI: 10.7717/peerj.11907
|View full text |Cite
|
Sign up to set email alerts
|

Association between C-Maf-inducing protein gene rs2287112 polymorphism and schizophrenia

Abstract: Background Schizophrenia is a severely multifactorial neuropsychiatric disorder, and the majority of cases are due to genetic variations. In this study, we evaluated the genetic association between the C-Maf-inducing protein (CMIP) gene and schizophrenia in the Han Chinese population. Methods In this case-control study, 761 schizophrenia patients and 775 healthy controls were recruited. Tag single-nucleotide polymorphisms (SNPs; rs12925980, rs2287112, rs3751859 and rs77700579) from the CMIP gene were genotyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Reported that the rs1800871 and rs18008729 variant alleles of IL10 were highly predictive of poor cognitive performance in patients with SCZ (Smeland et al, 2017). Fu et al (2021) reported that the CMIP allele variant rs2287112 was related to cognition ability in patients with SCZ. Based on GWAS data, Smeland et al (2017) who have related numerous genetic loci to cognitive traits, including intelligence, general cognition, reaction time, and verbalnumerical reasoning identified 21 loci that influence both SCZ and cognitive traits, including 2 loci that influence verbal-numerical reasoning, 6 loci that influence reaction time, and 14 that influence general cognitive function.…”
Section: Introductionmentioning
confidence: 99%
“…Reported that the rs1800871 and rs18008729 variant alleles of IL10 were highly predictive of poor cognitive performance in patients with SCZ (Smeland et al, 2017). Fu et al (2021) reported that the CMIP allele variant rs2287112 was related to cognition ability in patients with SCZ. Based on GWAS data, Smeland et al (2017) who have related numerous genetic loci to cognitive traits, including intelligence, general cognition, reaction time, and verbalnumerical reasoning identified 21 loci that influence both SCZ and cognitive traits, including 2 loci that influence verbal-numerical reasoning, 6 loci that influence reaction time, and 14 that influence general cognitive function.…”
Section: Introductionmentioning
confidence: 99%